Preparation of transparent conducting ZnO:Al films on glass substrates by ultrasonic spray technique - Gahtar, Abdelouahab; Benramache, Said; Benhaoua, Boubaker; Chabane, Foued (IOP Publishing, 2013)
Transparent conductive Al doped ZnO thin films were deposited by ultrasonic spray technique. Conditions of preparation have been optimized to get good quality. A set of aluminum (Al) doped ZnO (between 0 and 5 wt%) thin films were grown on glass substrate at 350 °C. Nanocrystalline films with a hexagonal wurtzite structure show a strong (002) preferred orientation. The maximum value of grain size G = 32.05 nm is attained of Al doped ZnO film with 3 wt%. All the films have low absorbance in the visible region, thus the films are transparent in the visible region; the band gap energy increased from 3.10 to 3.26 eV when Al concentration increased from 0 to 3 wt%. The electrical conductivity of the films increased from 7.5 to 15.2 (Ω·cm)−1. So the best results are achieved in Al doped ZnO film with 3 wt%.
Articale
Keywords: ZnO:Al; thin films; TCO; ultrasonic spray techniqu